2015
DOI: 10.5120/20197-2439
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Approach for Efficient Energy Utilization in Cloud Data Center

Abstract: Cloud computing has transmuted the IT industry on the whole and made easy to access the resources from anywhere and at anytime. These resources can be accessed as a service rather than as a product. Clients pay for the service used as per their requirement. The huge demand of cloud computing has given rise to the creation of hefty amount of data centers. These data centers consist of different types of resources and each resource is bound to its own power consumption scenario. Besides a number of benefits; Clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…These are in line with previous research [12,13] claimed that DVFS scheme would not give significant impact on network of less than 100 servers and switches since the scheme mainly manages voltage and frequency being used by servers and switches up and down and let them use the power although in idle state. In other study, it was reported that DVFS works fine to considerably reduce cloud energy consumption up to 1000 servers [14].…”
Section: Resultssupporting
confidence: 77%
“…These are in line with previous research [12,13] claimed that DVFS scheme would not give significant impact on network of less than 100 servers and switches since the scheme mainly manages voltage and frequency being used by servers and switches up and down and let them use the power although in idle state. In other study, it was reported that DVFS works fine to considerably reduce cloud energy consumption up to 1000 servers [14].…”
Section: Resultssupporting
confidence: 77%
“…Also, the servers should be kept switch off whenever they are not having any load and are idle [12]. Scaling (either up or down) of the servers dynamically aims for improvising the resource utilization and implementing the technique of load balance [19]. By applying all these ways, energy savings can be increased without affecting the efficient working of the servers.…”
Section: International Journal Of Computer Applications (0975 -8887) mentioning
confidence: 99%
“…1), the rate of increase, with respect to survey done in year 2003, 2007 and 2014, in the energy consumption [19] by the various sectors of the data centers is indicated.…”
Section: Fig 1 Energy Consumption Rate In the Data Centersmentioning
confidence: 99%
See 1 more Smart Citation
“… Carbon Aware Green Cloud Architecture [17]  Cloud Broker Architecture [25]  LPT and FPRRT [6]  Live Migration [13], including Server Consolidation [26] and Load Balancing [27].…”
Section: Techniques For Green Computingmentioning
confidence: 99%